Transcutaneous assessment of renal function in conscious rodents - Herrera Pérez, Zeneida; Weinfurter, Stefanie; Gretz, Norbert (JoVE. Video journal, 2016)
Glomerular filtration rate (GFR) is the gold standard to assess overall kidney function. However, traditional methods to evaluate GFR are cumbersome and time-consuming. In addition, serial blood or urine samples are required, with the associated stress for the experimental animals. A recent technique significantly reduces the investment in time and resources, minimizing the invasiveness and the animal stress, but being equally valid as the traditional approaches. The method measures transcutaneously renal function. Using an optical device and the exogenous renal marker fluorescein isothiocyanate (FITC)-sinistrin, this technique is capable of measuring the elimination kinetics of the marker through the skin. With neither blood nor urine samples nor the associated laboratory assays needed, the results of the transcutaneous measurement are almost instantaneously available. The method has been already validated in different species and successfully applied in several models of renal pathology. Moreover, due to its minimally invasive characteristics, it is suitable for sequential measurements within the same animal. Here is provided a detailed protocol to carry out the transcutaneous assessment of renal function in rodents.